ANALISIS PELAYANAN PEMBUATAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) DI KEPOLISIAN RESOT SELUMA - JUINDARTO, WEGI; ROSIDIN (JURNAL ILMIAH IDEA, 2024)
This research aims to find out how the quality of service provided by officers at the Seluma Police Station. In this study, a lot of data and facts were taken in the field from informants regarding the successes and complaints felt by the community regarding the quality of officers at the SKCK Seluma Police Station. This research approach uses observational research. The sources and techniques of data collection in this study were adjusted to the focus and objectives of the study. In accordance with the focus of the research, the source of data and data collection techniques is Seluma Police Station. Data analysis in this study was carried out during data collection, and after completion of data collection. Based on the results of direct research and interviews regarding the quality of services provided by SKCK Seluma Police, it can be concluded that during the implementation since 2015 until now it has been quite good. This can be seen from the 5 indicators from Parasuraman, namely Tangibles, Reliability, Respomsiviness, Assurance and Empathy